Treatment of Ethylene Glycol Poisoning with Oral Ethyl Alcohol - B. Achappa; D. Madi; T. Kanchan; N. K. Kishanlal (Case Reports in Medicine)
Ethylene glycol poisoning is not uncommon in India. The ill effects are primarily caused by its toxic metabolites: glycolic acid and oxalic acid. A 70-year-old female presented to our hospital with ataxia after ingestion of ethylene glycol. The reported case describes the management of ethylene glycol poisoning using oral ethyl alcohol as an alternative to the recommended intravenous ethyl alcohol and fomepizole that are not available for use in India. The need for high degree of clinical suspicion, targeted investigations, and early instigation of treatment is of prime importance in cases of ethylene glycol poisoning as it can lead to long-term complications or even death.